SUSTAINABLE SKILLS DAN STUDENT EMPLOYABILITY: PERSPEKTIF SUMBER DAYA MANUSIA DALAM PENGURANGAN KEMISKINAN (SDG 1) - Sari Budiarti; Anggun Permata Husda; Risya Rosyida (KINDAI, 2026)
This study examines the influence of Sustainable Skills encompassing Digital Literacy (DL), Problem-Solving Competency (PS), and Interpersonal Communication Skills (IC) on Student Employability (SE), mediated by Self-Directed Learning (SDL), Academic Resilience (AR), and Career Adaptability (CA). Grounded in Human Capital Theory (Strober, 1990) and the SDG 1 (No Poverty) framework, which posits that skills investment is central to breaking intergenerational poverty cycles, this study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) with 152 final-year management students at a private university in East Kalimantan. Results indicate that PS→AR (β=0.430, p<0.001), IC→CA (β=0.404, p<0.001), and DL→SDL (β=0.344, p<0.001) are all significant. At the outcome level, CA significantly predicts SE (β=0.373, p<0.001), while AR→SE (β=0.103, p=0.163) and SDL→SE (β=0.124, p=0.150) are not statistically significant. The model explains 17.1% of SE variance. These findings suggest that Career Adaptability is the dominant pathway linking sustainable skills to employability. The implications span both higher education curriculum development and policy reform aligned with SDG 1 targets, specifically through integrating career adaptability training, work-integrated learning, and interpersonal communication modules as mandatory curricular components. Keywords: sustainable skills; self-directed learning; academic resilience; career adaptability; SDG 1